Efficacy of several insecticide formulations against Periplaneta americana (L.) (Blattaria: Blattidae) in sewers (Bangladesh Journal of Medical Science, 2021)
Objective: Periplaneta americana (L.) is the most important invasive urban pests in sewers with high significance of public health. The aim of the study was to evaluate the efficacy of several insecticide formulations against American cockroaches in sewers.Methods: The population density of cockroaches was estimated before and after 1 and 5 months of the use of insecticides in sewer manholes. About 10 manholes were allocated for treatment of each insecticide formulation. Twenty manholes were allocated to controls (without the use of insecticides). Insecticides were considered effective achieving more than of 90% mean density reduction of cockroach population per a manhole.Results: The effectiveness of insecticide formulations in sewer manholes were considered effective after 1 month of insecticide treatments while the effectiveness of diazinon EC 5% and 0.05% formulations considered insufficient including 47.% and 19.5%mean density reduction of cockroaches, respectively. The effectiveness of chlorpyrifos EC 5% and Fog, and diazinon EC 5% were observed about 80.5%, 81.5%and 53.5% mean density reduction of cockroaches, respectively after 5 months of treatment while the other formulations did not achieve effectiveness.Conclusions: The insecticide formulations were considered effective and ineffective after 1 and 5 months of the use of insecticides, respectively. It would be more satisfied if insecticide formulations repeated every three months. A reasonable manner is using a combination of integrated pest management strategies recommending for successful P. americana control.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.569-585